Competition in the digital economy: An analysis of gatekeepers and regulations - Jan Büchel; Christian Rusche (Institut der deutschen Wirtschaft (IW), 2020)
The Digital Age saw the rise of several rapidly growing digital platforms with substantial market shares. Europe is a large target market for these globally operating platforms, although the majority of the most successful platforms come from the USA or Asia. In general, platform ecosystems differ from regular market environments: platforms extend to several markets and user groups at the same time and there is an increased degree of dynamics in the allocation of market shares in platform ecosystems, which leads to a pressure to constantly innovate. Platform ecosystems vary among themselves, not least due to the different types of platform business models or their varying impact on the whole sector. Recent developments have included the emergence of particularly overwhelming platforms, known as "gatekeepers", that control entire platform ecosystems. A gatekeeper obtains durable and stable significant market power in the market for intermediation services, it has a large impact on the underlying market(s) and it is vital for users from all sides of the platform. In contrast to conventional platforms, for gatekeepers the ability to contest any of the markets is significantly reduced from the perspective of competing platforms, not least due to significant lock-in effects for consumers. But too tight regulation and pre-emptive intervention without any occasion is not preferable. Rash and untailored action negatively affects the development and growth opportunities for online platforms that do not intend to breach existing competition rules. Indirectly, that harms consumers, by restricting innovation and the availability of products and services. Tailored procedures for individual large online platforms with gatekeeper power on a case-by-case basis are more expedient. Thereby the current regulatory framework is capable of acting and builds on established legal pillars. However, tailored modernisation and adaption, for example in merger control, is helpful for ensuring fair competition. Merger control can be empowered by including data and other synergies between involved enterprises into assessments in order to prevent the formation of gatekeepers.
Keywords: G34; K21; L12; 330